ANALISIS KRITIS TERHADAP PELAKSANAAN AKAD IJARAH PADA PEMBIAYAAN MULTIJASA SYARIAH: STUDI KASUS DI INDONESIA - Sumarta, Sumarta (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2022)
This study aims to conduct a critical analysis of the implementation of ijarah contracts in multi-service Islamic financing in Indonesia. Ijarah contracts are one of the main instruments in Islamic financing that adhere to Sharia law principles. Multi-service Islamic financing combines various services or goods in a single ijarah transaction, necessitating a critical analysis to ensure compliance with Sharia principles and fairness in its implementation. This study employs a qualitative method with a case study approach to understand how the process of implementing ijarah contracts is carried out, the main challenges faced, and the effectiveness of its implementation in achieving economic and Sharia objectives. Data were collected through in-depth interviews, field observations, and document analysis from several Islamic financial institutions in Indonesia. The research findings indicate that the process of identifying the goods or services to be leased is a crucial initial stage, involving detailed assessments of the specifications of the goods or services, market value, and expected benefits for the clients. The determination of rental prices is carried out with principles of fairness and transparency, using various methods such as market surveys and cost analysis. Agreements are drafted in the form of written contracts that meet the requirements of Sharia law and applicable regulations, with periodic monitoring and evaluation.